The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5604/01.3001.0012.2109
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of traffic signal timing using non-dominated sorting artificial bee colony algorithm for unsaturated intersections

Abstract: Vehicle delay and stops at intersections are considered targets for optimizing signal timing for an isolated intersection to overcome the limitations of the linear combination and single objective optimization method. A multi-objective optimization model of a fixed-time signal control parameter of unsaturated intersections is proposed under the constraint of the saturation level of approach and signal time range. The signal cycle and green time length of each phase were considered decision variables, and a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…ABC algorithm is widely used in optimizing traffic-related problems by previous researchers [60,68,96]. Zhao et al investigated a typical intersection as a case study at Lanzhou city [60].…”
Section: Artificial Bee Colony (Abc)mentioning
confidence: 99%
See 1 more Smart Citation
“…ABC algorithm is widely used in optimizing traffic-related problems by previous researchers [60,68,96]. Zhao et al investigated a typical intersection as a case study at Lanzhou city [60].…”
Section: Artificial Bee Colony (Abc)mentioning
confidence: 99%
“…ABC algorithm is widely used in optimizing traffic-related problems by previous researchers [60,68,96]. Zhao et al investigated a typical intersection as a case study at Lanzhou city [60]. The green time length of each phase of the signal cycle and signal cycle were considered as decision variables.…”
Section: Artificial Bee Colony (Abc)mentioning
confidence: 99%
“…To overcome the limitations of mono-objective optimization methods and linear programming, Zhao et al proposed a non-dominated sorting artificial bee colony (ABC) multi-objective algorithm for optimizing delay and vehicle stops at unsaturated isolated signalized intersections [68]. It was found that the suggested method could efficiently solve the Pareto front by improving the stops and delay simultaneously.…”
Section: Related Workmentioning
confidence: 99%
“…However, the general practice of optimizing signals to minimize delay does not necessarily minimize extra stops; hence emissions could increase [6][7][8]. Thereby, several studies [9][10][11] have been conducted to find a Pareto-optimal signal timings solution to balance delay and stops. Over time, in some studies, the balancing between delay and stops has shifted gradually to a tradeoff process between delay and sustainable metrics (e.g., fuel consumption and emissions) [6,7,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, most current literature does not differentiate between reducing fuel consumption and emissions [6,7,[9][10][11][12][13]. Thus, a question that needs to be raised is whether minimizing fuel consumption truly minimizes a few, some, or all emission types?…”
Section: Introductionmentioning
confidence: 99%